2014
DOI: 10.21608/esj.2014.3867
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcome of Sciatica after Redo Surgeries for Recurrent Lumbar Disc Herniation

Abstract: Background Data: Result of redo discectomies varies widely in the literature. This may be due to variability in inclusion criteria and associated pathologies which may alter results. We tried to evaluate the early outcome of recurrent sciatica after redo discectomies in highly selected cases and risk factors for poor outcome. Purpose: to assess the rate of success of redo lumbar discectomy in patients with recurrent sciatica. Study Design: A retrospective clinical case study Patients and Methods: A retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…On the other side, according to a similar study by Alkosha et al, 2 for management of patients with RLDH using conventional open discectomy, the early outcome percentage of satisfactory results was 87%, this is also in close proximity to our fore mentioned results. In another study by Fu et al, 11 also using traditional open discectomy for RLDH on 41 patients, clinical outcome was excellent or good in 78.3% of patients.…”
Section: Discussionsupporting
confidence: 87%
“…On the other side, according to a similar study by Alkosha et al, 2 for management of patients with RLDH using conventional open discectomy, the early outcome percentage of satisfactory results was 87%, this is also in close proximity to our fore mentioned results. In another study by Fu et al, 11 also using traditional open discectomy for RLDH on 41 patients, clinical outcome was excellent or good in 78.3% of patients.…”
Section: Discussionsupporting
confidence: 87%
“…16,18,19 Alkosha et al, 2 reported similar results for their series of recurrent lumbar discectomy patients, with a mean preoperative sciatica VAS of (8.97±1.03) which improved to (2.55±1.64) at 90 days postoperatively. Dasenbroke et al, 6 also reported a mean preoperative sciatica VAS score of almost 7 which improved at long-term follow-up (1-2 years postoperatively) to a mean of 1.6 in both the MID and OD groups.…”
Section: Discussionmentioning
confidence: 67%